China's remarkable economic growth - Knight, John B.; Ding, Sai. (Oxford : Oxford University Press, 2012)
China's economy has been growing at 10% per annum for the last three decades. This book considers one of the biggest questions facing contemporary economists: why and how is the Chinese economy growing so fast?
Includes bibliographical references and index.
Description based on print version record.
Keywords: Economic development -- China; China -- Economic policy -- 1976-2000.; China -- Economic policy -- 2000-